1992
DOI: 10.1046/j.1523-1739.1992.610047.x
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Selective Logging on Bird Species Diversity in a Guianan Rain Forest

Abstract: The composition and structure of the bird community were investigated in French Guiana (northeastern Amazonia) 1 year and 10 years after selective logging and compared with bird community composition and structure in undisturbed primary forest. A point‐count method was used in which 937 0.25‐ha sample quadrats were censused for 20 minutes each. Whereas logging removed little more than 3 trees/ha, 38% of the forest undergrowth was destroyed and a proportion of the canopy was opened or damaged. An overall 27–33%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
202
4
36

Year Published

2000
2000
2017
2017

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 309 publications
(256 citation statements)
references
References 36 publications
14
202
4
36
Order By: Relevance
“…The idea that mixed-species flocking species may be especially vulnerable was first raised by two classic studies of birds' responses to human disturbance [17,18] and was confirmed by Van Houtan et al [21]. All three of these studies were in Amazonia, with a unique system in which flocks defend interspecific territories [53].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The idea that mixed-species flocking species may be especially vulnerable was first raised by two classic studies of birds' responses to human disturbance [17,18] and was confirmed by Van Houtan et al [21]. All three of these studies were in Amazonia, with a unique system in which flocks defend interspecific territories [53].…”
Section: Discussionmentioning
confidence: 99%
“…Early reports on mixed-species flocks suggested that flocking species were particularly vulnerable to anthropogenic disturbance [17,18], and a number of studies have now investigated how flocks respond to fragmentation [19 -24] and to different land uses or successional stages [25 -30], with the near-universal finding of fewer and smaller flocks in more disturbed conditions. But the larger question of how and why the flocking phenomenon might influence how birds respond to land-use intensity is still unclear.…”
Section: Introductionmentioning
confidence: 99%
“…is relatively intolerant to selective logging (Thiollay 1992, 1997, Mason 1996. However, the response of golden-handed tamarin was unexpected, given that this specie is a generalist insectivore-frugivore (Pack et al 1999), and are widely found in secondary forest (Rylands & Keuroghlian 1988).…”
Section: Discussionmentioning
confidence: 99%
“…The first feature is the presence of relatively large areas without any history of RIL disturbance immediately adjacent to areas with RIL activities. One of the guidelines of RIL planning is the choice of areas with gentle topography and high concentrations of tree species with high commercial value (Thiollay 1992, Putz et al 2001). This fact allows for the persistence of ''islands'' of unlogged areas surrounded by logged ones.…”
Section: Discussionmentioning
confidence: 99%
“…In other tropical regions, little similarity was found between commercially exploited forest and pristine forest (Newmark 1991, Thiollay 1992, Mason 1996. In Caquipec, the high degree of similarity between the bird communities of undisturbed and disturbed forest indicates that the subsistence use of forest resources by Q'eqchi' communities may have low impact on the overall species composition.…”
Section: Human Impactmentioning
confidence: 99%